Presidential Address: Jews, Human Rights, and the Making of a New Canada - Abella, Irving (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2000)
AbstractFor the first half of the twentieth century, Canada was not a welcoming place for Jews. Xenophobia, nativism and anti-Semitism lay behind a wide range of quotas and restrictions that limited where Jews could live, be educated, work, or play. During the 1920s, 30s, and 40s, Nazi propaganda, a search for economic scapegoats, fear of communism, religious hatreds, and a general concern about recent rapid immigration all contributed to the problem. Then in the late 1940s, Canadian Jewish leaders launched an offensive against discriminatory practices. Through a publicity campaign and other efforts, they gradually won allies in church and service groups, the Association of Civil Liberties, and the new Ontario premier, Leslie Frost. By the 1960s, mechanisms to protect minorities were in place and Canada had begun the process of repealing its racist immigration laws. Efforts of Jewish leaders in the human rights movement of the 1940s and 50s played a central role in improving the treatment of minorities in late twentieth-century Canada.